Evaporation of liquid nitrogen droplets in superheated immiscible liquids. (November 2019) - Rebelo, N.; Zhao, H.; Nadal, F.; Garner, C.; Williams, A.
Highlights: The evaporation process of a liquid nitrogen droplet in different immiscible superheated bulk fluids has been quantified experimentally for the first time. The initial liquid nitrogen droplet size was found to have the dominant impact on the consequential evaporation rate. A scaling law based on the diffusion-controlled droplet evaporation process was found to be a good fit for the experimental data. A one-dimensional analytical heat transfer model with an empirical effective thermal conductivity has been developed to predict the droplet evaporation rate and the interface growth rate. Abstract: Liquid nitrogen or other cryogenic liquids have the potential to replace or augment current energy sources in cooling and power applications. This can be done by the rapid evaporation and expansion processes that occur when liquid nitrogen is injected into hotter fluids in mechanical expander systems. In this study, the evaporation process of single liquid nitrogen droplets when submerged into n -propanol, methanol, n -hexane, and n -pentane maintained at 294 K has been investigated experimentally and numerically. The evaporation process is quantified by tracking the growth rate of the resulting nitrogen vapour bubble that has an interface with the bulk liquid. The experimental data suggest that the bubble volume growth is proportional to the time and the bubble growth rate is mainly determined by the initial droplet size. A comparison between the four different bulk liquids indicates that the evaporation rate in n -pentane is the highest, possibly due to its low surface tension. A scaling law based on the pure diffusion-controlled evaporation of droplet in open air environment has been successfully implemented to scale the experimental data. The deviation between the scaling law predictions and the experimental data for 2-propanol, methanol and n-hexane vary between 4 and 30 % and the deviation for n -pentane was between 24 and 65 % . The more detailed bubble growth rates have been modelled by a heuristic one-dimensional, spherically symmetric quasi-steady-state confined model, which can predict the growth trend well but consistently underestimate the growth rate. A fixed effective thermal conductivity is then introduced to account for the complex dynamics of the droplet inside the bubble and the subsequent convective processes in the surrounding vapour, which leads to a satisfactory quantitative prediction of the growth rate.